Potential Efficacy of Panichchai Poultice in th Symptomatic Knee Azhalkeelvayu: A Case Study Report - Sathiyaseelan, V.; Vijayakumar, T. (Trincomalee Campus Eastern University,Sri Lanka, 2018)
Panichchai poultice is a traditional herbal remedy used to reduce vitiation of azhal humor (deranged vathathosam) in Mootu (joint). The poultice prepared with the only a pure herbal ingredient of Diospyros peregrine (Diospyros) fruits without seeds. Diospyros works a standard drug treatment for inflammation and cohesionof joints. It is frequently prescribed to control the symptoms of active arthritis. The Panichchai (Diospyros) is used in Siddha Traditional System of medicine to treat joint pain, swelling and inflammation. Osteoarthritis is known as Mulankalvatham or Azhalkeelvayu in Siddha medical system. The causes written by Siddhars for Azhalkeelvayu are blockage and dryness of the freely moving vatha in the joints which causes pain and swelling. The treatment involves elimination of blocked vatha from the joints through external application method. The above knowledge can be effective according to statistics from traditional practitioners. Hence the researchers tried to experiment the above knowledge scientifically. For the above destiny, the researchers purposively selected a ward patient who is with the joint pain, swelling and other inflammatory signs and symptoms of left knee joint diagnosed as osteoarthritis and according to the Sidhha philosophy diagnosed as Azhalkeelvayu with the diagnostic method of Envithapariksa. The patient treated with Panichchai fruit poultice for 42days applied every other day basis in the midst of patient’s jam-packed company. Progress improvement of osteoarthritis was recorded by fortnight observation and measuring knee joints for last six weeks. Results showed that the patient became symptoms and signs free of arthritis such as pain, swelling, restriction of movement,heat, redness and crepitus after application for scheduled period of poultice that ensured by subjective andobjective manner. It could be concluded that the fruit of Panichchai is effective for arthritis condition in external application six week as every other day. Further study should be performed with the adequate number of subjects.
Keywords: Azhalkeelvayu; Osteoarthritis; Diospyros peregrine